Daya Hambat Ekstrak Buah Delima Merah (Punica granatum Linn) Terhadap Pertumbuhan Porphyromonas gingivalis (The Inhibition of Red Pomegranate Fruit Extract (Punica granatum Linn) on The Growth Porphyromonas gingivalis) - Alvin Ananda Susetyo; Sri Hernawati; Dyah Indartin (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Background : Halitosis is a common complaint among general population. Porphyromonasgingivalis 33277 is the most frequent bacteria that cause halitosis. Pomegranate (Punicagranatum Linn) extract is used to control the number of Porphyromonas gingivalis population.Bioactive compound of pomegranate is polyphenol (Flavonoids and its derivate, tanins,ellagitanins) and Alkaloids. Objective : To Analyze the effectiveness of pomegranate againstInhibition of Porphyromonas gingivalis Materials and Metdhods :The research used discdiffusion method (Kirby-Bauer) with 7 treatment group (n=6). Petridish was filled with Agar andinoculated by Porphyromonas gingivalis. after 5 minutes, set up disk that previously immersed in100%, 50%, 25%, 12,5%, 6,25% pomegranate extract, distilled water (negative control) andClorhexidine 0,2% (positive control) on top. The Petridish were then placed in the desiccator andincubator at 37oC for 24 hours. Zone of Inhibition were measured using digital caliper by threeindependent observer and recorded in millimeter. The result of this study showed that there wereInhibition zone in all treatment group (except negative control). Results and Conclusions :Pomegranate extract had antibacterial activity against Porphyromonas gingivalis at 6,25 minimuminhibitory concentration.Keywords: Antibacterial activity, Punica granatum Linn extract, Porphyromonas gingivalis, Kirby-Bauer disk diffusion method.